Cevaplar

  • Eodev Kullanıcısı
2012-11-04T10:28:15+02:00

x³+y³'ü açarsak (x+y)²-3xy(x+y) olur burdanda (x+y)²-9=18 olur (x+y)²=27 (x+y)=3√₃ olur.

0
2012-11-04T10:43:19+02:00

xy.(x+y)=3 \ oldugundan \ x+y=3a \ dersek \ xy=1/a \ olur \\ x^2 + y^2 + 2xy =9a^2 \\ x^2 + y^2 = (9a^3 - 2)/a \ olur \\ x^3 + y^3 = (x + y) . (x^2 -xy + y^2) = 18 \\ x^2 + y^2 \ ve \ xy \ yerine \ yazarsak \\ (x+y) ((9a^3 - 2)/a - 1/a) = 18 \\ (3a) (3(a^3-1))/a =18 \\ 9(a^3-1)=18 \\ a^3-1=2 \\ a^3 = 3 \\ a=\sqrt[3]{3} \ olur \ yerine \ yazarsak \ \\ x+y=3\sqrt[3]{3} \ olur cozumum yanlissa mesaj yollarsin

0